Distributed Applications and Interoperable Systems 7th IFIP WG 6.1 International Conference, DAIS 2007, Paphos, Cyprus, June 6-8, 2007, Proccedings - Indulska, Jadwiga; Raymond, Kerry (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2007)
This book constitutes the refereed proceedings of the 7th IFIP WG 6.1 International Conference on Distributed Applications and Interoperable Systems, DAIS 2007, held in Paphos, Cyprus in June 2007. The DAIS conference was held as a joint event in federation with the 9th IFIP WG 6.1 International Conference on Formal Methods for Open Object-Based Distributed Systems (FMOODS 2007) and the 9th International Conference on Coordination Models and Languages (Coordination 2007). The 24 revised full papers presented were carefully reviewed and selected from 97 submissions. The papers address current research in context-awareness, adaptation, mobility, distributed applications and peer-to-peer computing, all of which relate to the sustainability of distributed applications and integrated systems. The papers are organized in topical sections on context-awareness, distributed applications, adaptation, peer-to-peer, and mobility.